Piperazine tethered heterocyclic hybrids: Synthesis, characterization, and in vitro studies from potent proteinase inhibitors to antiproliferative activity - Lairikyengbam Deepti Roy; Sajitha Remady; Adarsh KS; Jyotsna Kumar (Elsevier, 2024)
This study reports the synthesis and evaluation of the biological activity of a new series of piperazine analogues (PA) containing heterocyclic moieties. Structural analogies of all four novel synthesized drug candidates were confirmed using FT-IR, 1H-NMR, and HPLC- MS spectral analysis. The antimicrobial activity of all synthesized piperazine analogues was evaluated against Pseudomonas aeruginosa, Staphylococcus aureus, and Candida albicans using the agar well diffusion method. PA-2 and PA-3 exhibited strong antimicrobial activity against all tested pathogens, comparable to the standard. However, dose-dependent antimicrobial behaviour was observed for PA-4, while all three strains displayed strong resistance against, PA-1. The antioxidant activity of synthesized derivatives was assessed using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. The in vitro antioxidant activity results demonstrated that PA-3 displayed remarkable antioxidant activity with IC50 of 0.77 μg/mL compared to control (Gallic acid_0.75 μg/mL). PA-1 and PA-2 exhibited moderate antioxidant activity, while PA-4 showed the lowest antioxidant properties. Piperazine analogues were further investigated for their anti-inflammatory and antiproliferative activities using Proteinase Inhibitory Action and MTT assay against two breast cancer cell lines (MCF-7; MDA-MB-231). Results notified that PA-3 demonstrated encouraging anti-inflammatory (IC50 = 0.68 μg/mL) and antiproliferative (IC50 = 33.8 μg/mL) activities. The flow cytometric approach indicated that PA-4 raised the levels of H2DCFDA, signifying its cytotoxic nature against MDA- MB-231 cells. Furthermore, a gene expression analysis against CAIX gene (Hypoxia-regulated carbonic anhydrase- 9) as the target revealed that PA-3 significantly reduced the expression of CAIX genes in MDA-MB-231 cells, specifying a pronounced down-regulation effect on CAIX genes by PA-3. These results highlight the potential of the synthesized piperazine analogue PA- 3 as a promising candidate for further investigation in developing an anti-breast cancer drug against triple-negative breast cancer cells.